Health Behaviour in School-Aged Children, Sweden 2009/10 - Public Health Agency of Sweden (Public Health Agency of Sweden, 2014)
The survey Schoolchildren's Health Habits is a part of the international research project Health Behaviour in School-aged Children, created on the initiative of the World Health Organization. Sweden participated in the survey since 1985/86.

The study includes a random sample of 11 -, 13 - and 15-year-olds in each country. The survey covers questions about health, lifestyle, the environment at school and at home. The results are used to monitor the children's and young people's health over time and to identify areas requiring action to promote child and adolescent health. School children's health habits is a basis in the follow-up work in the public health policy goal area three, children and young people's living conditions.

The study that was conducted in 2009/10 is based on data from 11-, 13- and 15-year-olds, collected in November and December 2009. The survey was answered by nearly 7000 students in Sweden, representing a response rate of 88 percent.

Purpose:

The purpose with Health Behaviour in School-aged children is partly to increase the knowledge of habits and conditions that are considered to be important for children's health, and partly to monitor progress over time and to make comparisons with other countries.

Vart fjärde år deltar Sverige och ett fyrtiotal andra länder i en internationell undersökning, Skolbarns hälsovanor, av barns och ungas hälsa och hälsovanor. Sverige har deltagit i undersökningen, som Världshälsoorganisationen (WHO) samordnar, sedan 1985/86. Undersökningen omfattar ett slumpmässigt urval av 11-, 13- och 15-åringar i respektive land. Enkäten innefattar frågor om hälsa, levnadsvanor, miljön i skolan och i hemmet. Resultaten används för att följa upp barns och ungas hälsa över tid och för att identifiera områden som kräver insatser för att främja barns och ungas hälsa. Skolbarns hälsovanor är ett underlag i uppföljningsarbetet inom folkhälsopolitikens målområde tre, barns och ungas uppväxtvillkor.



Studien, som genomfördes 2009/10, bygger på uppgifter som 11-, 13- och 15-åringar lämnade i november-december 2009. Enkäten besvarades av närmare 7000 elever i Sverige, vilket motsvarar en svarsfrekvens på 88 procent.

Syfte:

Syftet med Skolbarns hälsovanor är dels att öka kunskapen om levnadsvanor och förhållanden som anses vara vara viktiga för barns hälsa, dels att följa utvecklingen över tid och att göra jämförelser med andra länder.
Svenska skolbarns hälsovanor 2009/10
Keywords: Persons; Personer; Activities of Daily Living; Aktiviteter i dagliga livet; Health Surveys; Hälsoundersökningar; Exercise; Träning; Population Surveillance; Populationsövervakning; Socioeconomic Factors; Socioekonomiska faktorer; Behavior; Beteende; Diet; Kost; Alcohol Drinking; Alkoholkonsumtion; Child; Barn; Family; Familj; Public Health; Folkhälsa; Health; Hälsa; Sex; Kön; Interpersonal Relations; Mellanmänskliga relationer; Mental Health; Psykisk hälsa; Tobacco, Smokeless; Rökfri tobak; Cross-Sectional Studies; Tvärsnittsstudier; Education; Utbildning; schools; skolor; schoolchildren; skolbarn; Energy Intake; Energiintag; Feeding Behavior; Ätbeteende; EDUCATION; UTBILDNING; HEALTH; HÄLSA; Health Sciences; Hälsovetenskap; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin